América Latina tras bambalinas Teorías conspirativas, usos y abusos - Senkman, Leonardo (2019)
This book reflects on social sciences, social history, and the history of ideas about the wide presence of conspiracy narratives in Latin America. The authors distinguish between the existence of plots -some successful, others failed- of another parallel phenomenon: conspiracy theories that interpret the world as the object of sinister machinations and clandestine intrigues. It is an epistemological logic, whose worldview and argumentative narrative function as a mobilizer of political and social forces.